(untitled) (Journal of the College of Basic Education, 2022)
The importance of the research lies in the extent of the impact of the learning-by-play strategy on learning some of the wrestling grips and the kinetic abilities of the learners, and from here was thinking about many solutions that focus on developing new means, including developing motor abilities and learning the grips that decide the outcome of the fight. The researchers used the experimental method on two groups and by designing equal groups, controlling and experimental, for the purpose of comparison. A sample of the Adhamiya club wrestlers were (10-12) years old and they were (24) educated, and the most important conclusions of the research were that the learning strategy exercises by playing had a positive effect on learning some grips wrestling. Among the recommendations is the need to use the learning by play strategy in teaching students for its effectiveness in facilitating the delivery of information to students.